A smart nanoplatform for enhanced photo-ferrotherapy of hepatocellular carcinoma - Tang, Longguang; Ling, Mingjian; Syeda, Madiha Zahra; Sun, Rui; He, Minghui; Mu, Qingchun; Zhu, Xiulong; Huang, Chunming; Cui, Liao (Frontiers in Bioengineering and Biotechnology, 2022)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths worldwide. Emerging therapies, such as ferroptosis mediated cancer therapy and phototherapy, offer new opportunities for HCC treatment. The combination of multiple treatments is often more effective than monotherapy, but many of the current treatments are prone to serious side effects, resulting in a serious decline in patients' quality of life. Therefore, the combination therapy of tumor in situ controllable activation will improve the efficacy and reduce side effects for precise treatment of tumor. Herein, we synthesized a GSH-activatable nanomedicine to synergize photothermal therapy (PTT) and ferrotherapy. We utilized a near-infrared dye SQ890 as both an iron-chelating and a photothermal converter agent, which was encapsulated with a GSH-sensitive polymer (PLGA-SS-mPEG), to attain the biocompatible SQ890@Fe nanoparticles (NPs). In the tumor microenvironment (TME), SQ890@Fe NPs showed a GSH-activated photothermal effect that could increase the Fenton reaction rate. Meanwhile, the depletion of GSH could further increase ferroptosis effect. In turn, the increasing radical generated by ferrotherapy could impair the formation of heat shock proteins (HSPs) which could amplify PTT effects by limiting the self-protection mechanism. Overall, the intelligent nanomedicine SQ890@Fe NPs combines ferrotherapy and PTT to enhance the efficacy and safety of cancer treatment through the mutual promotion of the two treatment mechanisms, providing a new dimension for tumor combination therapy.